2017
DOI: 10.1007/s13205-017-0879-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of TEM, SHV, and CTX-M genes of extended-spectrum β-lactamase-producing Escherichia coli strains isolated from urinary tract infections in adults

Abstract: Urinary tract infections (UTIs) are one of the major sources of widespread infectious diseases in the community as well as in the hospitals which increase the cause of morbidity and mortality. Prevalence of extended-spectrum-β-lactamase (ESBL)-producing uropathogenic E. coli isolates has been found to be increased rapidly across the world. The present study was undertaken to find out the frequency of bla , bla and bla genes among E. coli isolates from UTI and detect their sensitivity pattern. A total of 112 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 30 publications
14
23
2
Order By: Relevance
“…In this study, we found a high proportion of E. coli (64.9%) isolates to be multidrug resistant (MDR). Our findings on MDR bacteria in UTI cases are compatible with the reports from different parts of the world, including Nepal [17,28,32,33]. ese MDR E. coli strains are common in the study hospital as we previously reported the similar findings in pediatric UTI cases [34].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found a high proportion of E. coli (64.9%) isolates to be multidrug resistant (MDR). Our findings on MDR bacteria in UTI cases are compatible with the reports from different parts of the world, including Nepal [17,28,32,33]. ese MDR E. coli strains are common in the study hospital as we previously reported the similar findings in pediatric UTI cases [34].…”
Section: Discussionsupporting
confidence: 92%
“…Alongside, we observed diverse genotypes of ESBL among E coli isolates. In this study, bla-TEM (83.8%) was the most predominant genotype of ESBL among E coli isolates, which is well supported by a recent Indian study [32]. However, the bla-CTX-M gene has been described as the most common genotype of ESBL among enterobacteriaceae in several literatures [40][41][42].…”
Section: Discussionsupporting
confidence: 87%
“…These results are of paramount significance to public health considering the fact that ESBL genes are plasmid-mediated and are usually associated with transposons and insertion sequences [36, 37, 38, 39], which imply that they are easily transmissible to other strains of the same or different species. The exchange of plasmids between bacterial cells and the integration of resistance genes into transferrable genetic elements plays a major role in acquisition and dissemination of antibiotic resistance genes among bacteria isolates [40, 41, 42, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials represent the standard of care for UTIs, albeit treatment has steadily become more difficult due to the increasing prevalence of multidrug-resistant (MDR) organisms, specifically, Gram-negative isolates. Common antimicrobials used for the treatment of UTIs, such as fluoroquinolones and ␤-lactams, are often no longer effective, with upwards of 50% of urinary tract infections now caused by MDR organisms (4,5).…”
mentioning
confidence: 99%